Rock around the clock [videorecording (DVD)] - Sears, Fred F.; Haley, Bill, 1925-1981; Martínez, Tony; Bell, Freddie; Freed, Alan (Sony Pictures Home Entertainment, 2006)
A big band promoter and musicians discover a fun-loving group of kids moving to a new kind of beat called rock 'n' roll.